The Required Conditions for an Arabic Manuscript and Its Verifier (A Descriptive and Analytical Study) - Mohamed Rady Mohamed Elpaz Elsheakh; Mohd Syauqi Bin Arshad (Diwan Media Pustaka, 2024)
This research paper is entitled “The Conditions that Must be Met in the Arabic Manuscript and its Investigator. We try to explain the importance of the Arabic manuscript، its scientific value and the conditions that must be met in it and its investigator، a descriptive and analytical study، because manuscripts have a great impact on the advancement and development of Arab knowledge and then human knowledge، because Arab culture is a global culture because it includes the Arab and Islamic heritage، because the Islamic state in the ages of its civilization and urbanization extended its influence over a wide area of the world at that time، in the continents of the ancient world Asia، Africa and Europe، and then the sources of its heritage varied between the Arabs، Romans، Persians، China، India، Greece All this and others gave the Arab and Islamic heritage a great scientific value، and our glorious scholars left a huge legacy of manuscripts in all kinds of sciences and knowledge at that time، and then it was necessary to shed light on the manuscripts and indicate the conditions that must be met in them and in their investigator، and highlight the scientific value of them: “Manuscripts and their scientific value”، the second discussion is titled: “Conditions to be met in manuscripts”، the third discussion is titled: “Conditions to be met in the investigator”، then comes the conclusion with the most important results reached by the research، and finally a list of sources and references.